1980
DOI: 10.1111/j.1464-410x.1980.tb03110.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Urethral Sensation in Clinical Urology

Abstract: The results of testing posterior urethral electrosensitivity in a variety of urological conditions are demonstrated and the relationship between urethral sensitivity and the standard urodynamic investigations discussed. The clinical features of a group of patients with urethral hyposensitivity are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 3 publications
0
28
0
Order By: Relevance
“…Although electrical current is not a physiological stimulus for sensory receptors, it has been used for several decades both in diagnostic and therapeutic modalities in LUTdysfunctions [Frimodt-Moller, 1972;Katona, 1975;Kieswetter, 1977;Powell and Feneley, 1980;Madersbacher et al, 1982;Wyndaele, 1993;Primus et al, 1996]. Determination of electrical thresholds in the LUT was ¢rst described by Frankl-Hochwart and Zuckerlandl in the 19th century, and it was reintroduced by Markland et al in 1965.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although electrical current is not a physiological stimulus for sensory receptors, it has been used for several decades both in diagnostic and therapeutic modalities in LUTdysfunctions [Frimodt-Moller, 1972;Katona, 1975;Kieswetter, 1977;Powell and Feneley, 1980;Madersbacher et al, 1982;Wyndaele, 1993;Primus et al, 1996]. Determination of electrical thresholds in the LUT was ¢rst described by Frankl-Hochwart and Zuckerlandl in the 19th century, and it was reintroduced by Markland et al in 1965.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation is widely used in neurophysiology because of the accuracy and reproducibility of the current parameters. Although electrical current is a nonphysiological stimulus for sensory receptors, it has been successively used in diagnostic and therapeutic approaches for neurogenic LUT dysfunctions [Frimodt-Moller, 1972;Katona, 1975;Kieswetter, 1977;Powell and Feneley, 1980;Madersbacher et al, 1982;Wyndaele, 1993;Primus et al, 1996]. This raises the question whether electrical stimulation also can be used to get an objective ¢gure that represents sensation elicited by bladder ¢lling.…”
Section: Introductionmentioning
confidence: 99%
“…Kiesswetter [7] first tested mucosal electrosensi tivity to both bladder and urethra with a double-bar relled catheter, bearing two wire electrodes. Powell and Feneley [8] specifically tried to assess the importance of…”
Section: Introductionmentioning
confidence: 99%
“…Geirsson and Fall [15] recently showed that the excitatory bladder response in humans is induced by distension and cooling of the urethra. Powell and Feneley [14] tested the sensitivity of the posterior urethra in more than 100 patients in the UK and found that subjects with BOO and urge, but not detrusor instability detected by cystometry, had lower sensory thresholds than had control patients. Therefore, these authors concluded that there is a correlation between urethral sensitivity and the ®rst desire to void.…”
Section: Discussionmentioning
confidence: 99%